Literasi Gizi Remaja Melalui Permainan Edukasi Goaksi (Go Aksi Bergizi) - Rini Harianti; Imelda Fitri; Hotmauli Hotmauli; Brilian Dini MA Iballa; Fenny Anita; Ully Astuti Siregar (Universitas Lancang Kuning, 2022)
Nutritional problems in adolescents are increasingly complex, one of which is nutritional anemia and skipping breakfast. It happens because of limited knowledge about balanced nutrition in adolescents. With the increasing nutritional problems of adolescents, the Community Service (PKM) team collaborates with partners, namely students of SMAN 1 Perhentian Raja, Kampar to carry out adolescents' nutrition literacy through the educational game GOAKSI (Go Aksi Bergizi). This activity effort to convey adolescent nutritional literacy through counseling the contents of my plate in meeting nutrition needs. The PKM was attended by 28 student 11th graders. All students were able to understand well the concept of balanced nutrition through the contents of my plate by an increase in the average value of knowledge from 5.4 to 8.0 (pre-test and post-test results) of 2.6 points. It is hoped that PKM activities can be carried out continuously with different topics, so that the formation of knowledge and positive attitudes of adolescents in fulfilling balanced nutrition and good food habits in overcoming adolescent nutritional problems.